THE IMPORTANCE OF PROTECTION OF AUTOCHTHONOUS DAIRY PRODUCTS AND POSSIBILITIES TO INCREASE AUTOCHTHONOUS DAIRY PRODUCTS PRODUCTION OBSERVED AS FACTORS IN THE DEVELOPMENT OF THE MUNICIPALITY OF ŠTRPCE - Slavica Arsić; Nataša Kljajić; Mirjana Savić (Ekonomika Poljoprivrede (1979), 2018)
Security situation in Kosovo and Metohija and traffic circumstances – in other words - distance between the municipality of Štrpce and bigger consumer centres in Serbia and other factors restrict milk procession in the existing diary plant and on agricultural husbandries mostly into durable white cheese and cheese brine. The procession of milk into cheese and dairy products with short term durability is significantly less performed, because of the above mentioned reasons.